2020
DOI: 10.3389/fmicb.2019.02994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Four Sexual Differentiation Process Proteins (isp4/SDPs) in Chaetomium thermophilum and Thermomyces lanuginosus Reveals Their Distinct Roles in Development

Abstract: Fungal sexual development requires the involvement of a large number of functional genes. Fungal genes encoding sexual differentiation process proteins (SDPs), isps, have been known for decades. isp4/SDP and its homologs function as oligopeptide transporters (OPTs), yet their roles in reproduction are unknown. Here, we genetically analyzed all four isp4/SDP homologs in the sexual species Chaetomium thermophilum and asexual species Thermomyces lanuginosus. Using single gene deletion mutants, we found that T. la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…T. lanuginosus could absorb arabinose well for growth and degrade xylan efficiently but could not utilize cellulose [41,59,60] while C. thermophilum could degrade cellulose well, showing a partial complementary in their ability to degrade lignocellulose. What's more, a study had shown that the thermophilic fungi C. thermophilum and T. lanuginosus coexisted in the same habitats, which had relatively high temperatures and lignocellulose-rich composts [61]. So we suppose that C. thermophilum may be symbiotic with T. lanuginosus, which needs more effort for further study.…”
Section: Discussionmentioning
confidence: 89%
“…T. lanuginosus could absorb arabinose well for growth and degrade xylan efficiently but could not utilize cellulose [41,59,60] while C. thermophilum could degrade cellulose well, showing a partial complementary in their ability to degrade lignocellulose. What's more, a study had shown that the thermophilic fungi C. thermophilum and T. lanuginosus coexisted in the same habitats, which had relatively high temperatures and lignocellulose-rich composts [61]. So we suppose that C. thermophilum may be symbiotic with T. lanuginosus, which needs more effort for further study.…”
Section: Discussionmentioning
confidence: 89%
“…As we can see from the results, the expression of the sexual differentiation process protein Isp4 (A0A067N4P4) was significantly down-regulated in the HCO group. Sexual differentiation process proteins have been studied in Schizosaccharomyces pombe and some other fungi [ 31 , 32 ], and isp4 has been found to be up-regulated by nitrogen-starvation-induced meiosis. A0A067N4P4, which might be involved in meiosis and reproduction in P. ostreatus , has 53.0% amino-acid sequence identity with Isp4 in S. pombe (NP_595653).…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantageous to all of the aforementioned methods is, however, that only ectopic chromosomal integrations without any knowledge of the gene locus, number of integration events or expression levels were possible in the past. Although deletion mutants have already been created in C. thermophilum wild-type mycelia, the procedure appeared to be inefficient and imperfect (e.g., some desired strains were impossible to obtain despite screening thousands of candidate transformants) [ 21 ]. To circumvent these difficulties, we aimed to develop a homologous recombination (HR)-compatible C. thermophilum strain to conceive precise gene modification/replacement experiments, as HR allows efficient incorporation, expression control, and modification of desired target genes, respectively.…”
Section: Introductionmentioning
confidence: 99%